Developmental osteology of Sciaenops ocellatus and Cynoscion nebulosus (Teleostei: Sciaenidae), economically important sciaenids from the western Atlantic. (17th April 2015) - Kubicek, Kole M.; Conway, Kevin W.
Abstract: The adult skeleton in members of the economically important Sciaenidae is well documented, but information on earlier developmental stages is sparse and often focused on a particular character complex. To generate information on skeletal development in sciaenid fishes, we investigated the ontogeny of the entire skeleton in the western Atlantic Sciaenops ocellatus (Red drum) and Cynoscion nebulosus (Spotted seatrout), which are the focus of successful captive rearing programmes within the southern United States. Development of the skeleton (excluding the basisphenoid and sclerotic bones) is complete in S. ocellatus and C. nebulosus at 14.4 mm SL and 13.5 mm SL, respectively. The basisphenoid did not appear until later in development (21.9 mm SL in S. ocellatus and 19.5 mm SL in C. nebulosus ), while the sclerotic bones are not present in the material examined. No major differences are identified between the ossification sequences compiled for each species. Cynoscion nebulosus exhibited variation in the presence/absence of two elements, supraneural 1 and the coronomeckelian. Lastly, we compile and compare available information on skeletal development across members of the Sciaenidae and compare the sequence of ossification compiled for S. ocellatus to that available for Danio rerio and Salminus brasiliensis (entire skeleton), and Chanos chanos (cranium only).